2021
DOI: 10.3389/fvets.2021.645456
|View full text |Cite
|
Sign up to set email alerts
|

The Isolation and Replication of African Swine Fever Virus in Primary Renal-Derived Swine Macrophages

Abstract: African swine fever virus (ASFV) causes hemorrhagic disease in domestic pigs by replicating mainly in monocyte/macrophage lineages. Various primary cells including pulmonary alveolar macrophages have been used for the propagation of ASFV on this account. However, ethical constraints and consistency problems exist as it is necessary to harvest same phenotype of primary cells in order to continue a study. We suggested renal-derived swine macrophages as a novel primary cell candidate to address these issues. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
(47 reference statements)
0
13
0
Order By: Relevance
“…Despite the many advantages of PAMs, working with these primary cells includes some disadvantages, such as high time consumption, expensive cell extraction, and animal welfare considerations [ 18 ]. In addition, other issues are the high variation hindering consistent macrophage phenotypes among different pigs and the low reproducibility from day to day [ 49 , 50 ].…”
Section: Porcine Macrophages: the Main Target Of African Swine Fever ...mentioning
confidence: 99%
See 4 more Smart Citations
“…Despite the many advantages of PAMs, working with these primary cells includes some disadvantages, such as high time consumption, expensive cell extraction, and animal welfare considerations [ 18 ]. In addition, other issues are the high variation hindering consistent macrophage phenotypes among different pigs and the low reproducibility from day to day [ 49 , 50 ].…”
Section: Porcine Macrophages: the Main Target Of African Swine Fever ...mentioning
confidence: 99%
“…Macrophages can be efficiently isolated from primary porcine kidney cell cultures [ 51 ], and Oh and colleagues recently characterized these cells as renal-derived macrophages presenting the molecular and morphological characteristics of monocyte/macrophage lineage, with high continuity and reproducibility. In detail, immunocytochemistry analyses revealed that these cells expressed macrophage markers CD163, CD172a, and Iba1 [ 50 ], indicating that they were a mature macrophage population, and most importantly, that they were susceptible to infection with both wild-type (MW039157) and cell-adapted (MW287337) ASFV genotype II.…”
Section: Porcine Macrophages: the Main Target Of African Swine Fever ...mentioning
confidence: 99%
See 3 more Smart Citations